(A study cassava flour substitution for wheat flour in istants Noodle Processing - Neffi Ridwan, Indra; Rosadi, Kukuh; Abdurahman, Dede; Suharto, Ign.; Sutisna, Nana (Warta Industri Hasil Pertanian, 1991)
The research was aimed at studying the substitution rate of cassava flour for wheat flour in the production of instants noodle.The preliminary study was conducted to find out the suitable rate of cassava flour substitution.The following percentages were used :10,15,20,25,30,35,50,and 100%,The three best result of these,20,30,and 35%, Were used in the main study. Proximate chemical analysis and organoleptic test were conducted on the instant noodle produced.The results showed that the use of cassava flour is acceptable up to 35% substitution. The higher the substitution the lower the noodle quality would be.